Bioactive Polysaccharide Materials for Modern Wound Healing - Maver, Tina (Biobased Polymers,, 2018)
This is the first concise book that includes different aspects of naturally-derived components for wound healing. It presents the first exhaustive review of modern techniques in wound dressing development. With a growing, ageing population and the rapid growth of the wound-care market, the authors explore the current trend of bio-based products (active components and host materials) in this field. After a short introduction into modern solutions in wound-care and modern techniques in wound-dressing development, the authors, leaders in the field, explore natural-based components (drugs, extracts, materials etc.); safety and efficiency assessments (biocompatibility, cytotoxicity and in vitro performance etc.); and model films as a platform for the development of new wound dressings.